Functional and structural characterization of human heteromeric 5-HT3 receptors - Mazzarini Dimarco, Albano (2019)
5 HT3 receptors are the only serotonin (5-HT) receptors that belong to the Cys-loop receptor family. They mediate fast excitatory transmission in central and peripheral nervous system. Five different subunits (A-E) have been identified in humans. The A subunit is able to form homomeric receptors (5-HT3A), and it can combine with the B subunit to form heteromeric receptors. We here evaluated if the C-E subunits can combine with the A to form heteromeric receptors. To this end, we constructed a high-conductance A subunit (AHC) that allowed to obtain single-channel events. After expression of the AHC we observed events with an amplitude of ~4.7 pA corresponding to the 5 HT3AHC receptor. However, when AHC was expressed in combination with one of the CE subunits, events with different amplitudes were detected, thus confirming the expression of heteromeric receptors. From macroscopic currents we observed an increase in the 5-HT EC50 value for each of the heteromeric receptors with respect to that for the 5 HT3AHC receptor. In-silico studies provided insights into the contribution of the different subunits to the 5-HT binding site. Our results demonstrate that C-E subunits can combine with the A subunit to form heteromeric receptors. These results bring structural and functional details about the different human 5-HT3 receptors and will contribute to the development of selective therapies targeting this receptor family.